Mental health status and change in living rhythms among college students in China during the COVID-19 pandemic: A large-scale survey - Chen, Rong-ning; Liang, Shun-wei; Peng, Yang; Li, Xue-guo; Chen, Jian-bin; Tang, Si-yao; Zhao, Jing-bo (Journal of psychosomatic research, 2020)
•7.7% of college students showed depressive symptoms during the COVID-19 pandemic.•College students with depressive symptoms had low regulatory emotional self-efficacy.•Browsing COVID-19 information over 3 h per day was related to depressive symptoms.•Unfavorable living rhythms were associated with depressive symptoms.•Pay attention to college students' mental health during the COVID-19 pandemic.